2006
DOI: 10.1002/jcla.20100
|View full text |Cite
|
Sign up to set email alerts
|

Presence of immunounreactive albumin in the urine of diabetic patients

Abstract: Recent studies have demonstrated that conventional immunochemical assays underestimate urinary albumin concentration because of the presence of immunounreactive albumin. It has been reported that intact urinary albumin in 24-hr diabetic urine samples could be detected as total concentration (immunoreactive+immunounreactive) by an HPLC method based on size exclusion chromatography. The aim of this study was to investigate urinary albumin concentration in diabetic spot urine samples by comparing the HPLC method … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 27 publications
1
2
0
Order By: Relevance
“…This result suggests that at least part of the urinary albumin in cardiovascular disease becomes fragmented under reducing condition. Our results are partly congruent with those reported by Osicka et al 25) and we have previously observed a similar decrease in the albumin content in patients with diabetic mellitus 26) . The degree to which this unstable albumin relates to the decreased reactivity of the antibody is at present unclear and further examination is warranted.…”
Section: Resultssupporting
confidence: 94%
“…This result suggests that at least part of the urinary albumin in cardiovascular disease becomes fragmented under reducing condition. Our results are partly congruent with those reported by Osicka et al 25) and we have previously observed a similar decrease in the albumin content in patients with diabetic mellitus 26) . The degree to which this unstable albumin relates to the decreased reactivity of the antibody is at present unclear and further examination is warranted.…”
Section: Resultssupporting
confidence: 94%
“…46 Immuno-unreactive intact albumin has also been found in urine from diabetic patients using high performance liquid chromatography (HPLC) analysis, which measures both immunoreactive intact albumin and immuno-unreactive intact albumin (total albumin). [47][48][49] Immuno-unreactive intact albumin has been isolated from diabetic urine through the use of anti-albumin immunosubtraction chromatography and HPLC purification. 50 The immunochemical nonreactive nature of this immunounreactive intact albumin molecule may be due to the fact that the epitope is altered by a conformational change as a result of incomplete processing by the lysosomal pathway, which is compromised in diabetes but not in healthy subjects, 28,40 or due to the attachment of ligands such as glucose or fatty acids which are increased in diabetes.…”
Section: Composition Of Albumin In Urinementioning
confidence: 99%
“…Therefore, immunoassays might underestimate and underdiagnose microalbuminuria. Furthermore, it is not clear whether there is a difference in the relative amount of urinary immunoreactive and immuno‐unreactive albumin among primary diseases since most reports concern albuminuria measured in diabetes .…”
Section: Introductionmentioning
confidence: 99%